Has the Electrical Laboratory of Subang State Polytechnic Applied Occupational Safety and Health? Evaluation Report in 2019 - Adhan Efendi; Yohanes Sinung Nugroho (Automotive Experiences, 2019)
The application of Occupational Safety and Health (OSH) is essential in vocational institutions that have a high risk of accidents. Therefore, this study aims to evaluate the application of OSH in the Electrical Laboratory of Subang State Polytechnic using a qualitative descriptive method through observation and interviews. The results of this study indicate that aspects of the application of the standard Personal Protective Equipment (PPE) and the use of practical work standards have a score of 66.25% and 62.5%, respectively. Meanwhile, the application of room standards seen from the four main indicators, namely furniture, equipment, educational media, and supporting equipment obtained a total score of 91% (high feasibility). In conclusion, the application of the PPE standard and practical work standard must be considered in detail to improve the overall OSH score.